Investigations into Isoniazid Treated Mycobacterium tuberculosis by Electrospray Mass Spectrometry Reveals New Insights into Its Lipid Composition. (19th June 2018) - Pal, Rahul; Hameed, Saif; Sabareesh, Varatharajan; Kumar, Parveen; Singh, Sarman; Fatima, Zeeshan
Abstract : Many of the earlier studies involving the effect of isoniazid (INH) treatment have solely focused on the fatty acyl (FA) category of Mycobacterium tuberculosis (MTB) lipids. This motivated us with the major interest to examine the impact of INH on various other categories of MTB lipids. Towards this, we chose to interpret our mass spectral data (LC-ESI-MS) by a standalone software, MS-LAMP, in which "Mtb LipidDB" was integrated. Analysis by MS-LAMP revealed that INH treatment can alter the composition of "glycerolipids (GLs)" and "glycerophospholipids (GPLs)" categories of MTB lipids, in addition to the variations to FA category. Interpretation by "MycoMass" database yielded similar results as that of Mtb LipidDB, except that significant alterations to polyketides (PKs) category also were observed. Probing biosynthetic pathways of certain key lipids belonging to any of GLs, GPLs, and PKs categories can be attractive target(s) for drug discovery or can be useful to identify means to overcome drug resistance or to obtain insights into the causal factors of virulence. To the best of our knowledge, this is the first report hinting at the influence of INH on GLs, GPLs, and PKs of MTB.